2019
DOI: 10.3928/01913913-20190610-01
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing Factors, Ophthalmic Manifestations, and Radiological Findings in Children With Cerebral Visual Impairment

Abstract: Purpose: To describe predisposing factors, ophthalmic manifestations, and magnetic resonance imaging (MRI) findings in children with cerebral visual impairment. Methods: A retrospective cross-sectional analysis of patients younger than 16 years with neuroradiological and clinical evidence of retrogeniculate visual pathway pathology was performed. Detailed histories, ophthalmic examinations, and MRI findings were compiled and analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The proportion of male to female was 1.6:1 in our study, which is similar to observations made in other studies. [ 14 17 ] As no sex predilection has been reported in CVI, this gender inequality may be because of the societal norms. It has been observed that ocular diseases in males are prioritized more than females in both adults and children in low- and middle-income countries, including India.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The proportion of male to female was 1.6:1 in our study, which is similar to observations made in other studies. [ 14 17 ] As no sex predilection has been reported in CVI, this gender inequality may be because of the societal norms. It has been observed that ocular diseases in males are prioritized more than females in both adults and children in low- and middle-income countries, including India.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 20 ] Our study reports a late age at presentation with a median age of 4 years in comparison to other studies where they reported a young age at presentation. [ 8 15 17 ] In the Pehere et al . [ 15 ] and Ganesh et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations